Synergistic Antioxidant Activity of Roselle (Hibiscus sabdariffa L.) and Basil (Ocimum sanctum L.) Extract Syrup in Rats Exposed to Oxidative Stress from Used Cooking Oil - Iqbal, Muhammad; Mustaina, Mustaina; Yusuf, Nur Fajrin Maulana (Majalah Kesehatan Indonesia, 2025)
This study aimed to evaluate the antioxidant effect of a syrup combining Hibiscus sabdariffa L. (roselle) and Ocimum sanctum L. (basil) extracts in male rats exposed to oxidative stress induced by used cooking oil (UCO). A randomized controlled design was applied using six treatment groups, including single and combined extract syrups. Plasma malondialdehyde (MDA) levels, an indicator of lipid peroxidation, were measured before induction, after UCO exposure, and following treatment. Results showed a significant rise in MDA levels after UCO induction, confirming oxidative stress. Administration of roselle–basil syrup markedly reduced plasma MDA compared with the induced control (p < 0.05). The optimal formulation achieved up to a 96–97% reduction in MDA levels, indicating strong antioxidant efficacy. This effect is attributed to the synergistic action of anthocyanins from roselle and eugenol and rosmarinic acid from basil, which act as radical scavengers and metal chelators. These findings validate the synergistic potential of the roselle–basil combination in mitigating oxidative stress and lipid peroxidation. The study highlights its promise as a natural, safe, and locally sourced antioxidant formulation, offering a foundation for developing functional beverages or nutraceutical products aimed at preventing oxidative damage from dietary lipid oxidation.